2009
DOI: 10.1016/j.ejpain.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute gouty arthritis on sleep patterns: A preclinical study

Abstract: These data suggest that a nociceptive stimulus, induced by the intra-articular administration of uric acid, alters the sleep-wake equilibrium with REM sleep being particularly altered. However, further research concerning pain-sleep interaction is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 75 publications
(113 reference statements)
1
10
0
Order By: Relevance
“…The present study confirmed a causal relationship between sleep disturbance and pain in control animals, as evidenced by an increase in AW time and decreases in QS and PS times. This is consistent with the findings of previous studies on the effects of pain on sleep [39][40][41] . We applied telemetric recording without interruption of rat activity for 24 h and differentiated between the light (resting) and dark (active) phases.…”
Section: Discussionsupporting
confidence: 83%
“…The present study confirmed a causal relationship between sleep disturbance and pain in control animals, as evidenced by an increase in AW time and decreases in QS and PS times. This is consistent with the findings of previous studies on the effects of pain on sleep [39][40][41] . We applied telemetric recording without interruption of rat activity for 24 h and differentiated between the light (resting) and dark (active) phases.…”
Section: Discussionsupporting
confidence: 83%
“…Gout patients described sleep disruption, with problems falling asleep and gout flares waking them up. A recent clinical study showing an independent association of gout with sleep problems [43] and a pre-clinical study showing altered rapid eye movement sleep and total sleep time after an intra-articular injection of uric acid [44] are highly supportive. Sleep disturbances are common in rheumatoid arthritis [45,46], another inflammatory arthritis, and respond to treatment with disease-modifying agents that target cytokines [47].…”
Section: Discussionmentioning
confidence: 99%
“…First, we cannot directly measure sleep, disruption of which is an often-reported problem in chronic pain patients [48] and has been observed in some studies of rats with nerve injury or experimental arthritis [15,28,40,60]. By documenting periods and patterns of inactivity, the HCM system can, to some extent, provide a reasonable estimate of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Further, if the animal is indeed experiencing spontaneous pain similar to humans, there should be an impact on its daily life activity and affective state, behaviors we will herein refer to as “quality of life” measures. To date, such studies in rodents have concentrated on the rat and included measures of daily life such as sleep [15,24,28,40,55,60] and locomotion [6,16,27,33,61]. Results from these and other studies on affective state changes following chronic injury are mixed.…”
Section: Introductionmentioning
confidence: 99%